Private sector engagement in the COVID-19 response: experiences and lessons from the Democratic Republic of Congo, Nigeria, Senegal and Uganda - Steven N. Kabwama; Suzanne N. Kiwanuka; Mala Ali Mapatano; Olufunmilayo I. Fawole; Ibrahima Seck; Alice Namale; Rawlance Ndejjo; Susan Kizito; Fred Monje; Marc Bosonkie; Landry Egbende; Segun Bello; et al. (BMC, 2022)
Abstract Background Private entities play a major role in health globally. However, their contribution has not been fully optimized to strengthen delivery of public health services. The COVID-19 pandemic has overwhelmed health systems and precipitated coalitions between public and private sectors to address critical gaps in the response. We conducted a study to document the public and private sector partnerships and engagements to inform current and future responses to public health emergencies. Methods This was a multi-country cross-sectional study conducted in the Democratic Republic of Congo, Nigeria, Senegal and Uganda between November 2020 and March 2021 to assess responses to the COVID-19 pandemic. We conducted a scoping literature review and key informant interviews (KIIs) with private and public health sector stakeholders. The literature reviewed included COVID-19 country guidelines and response plans, program reports and peer-reviewed and non-peer-reviewed publications. KIIs elicited information on country approaches and response strategies specifically the engagement of the private sector in any of the strategic response operations. Results Across the 4 countries, private sector strengthened laboratory systems, COVID-19 case management, risk communication and health service continuity. In the DRC and Nigeria, private entities supported contact tracing and surveillance activities. Across the 4 countries, the private sector supported expansion of access to COVID-19 testing services through establishing partnerships with the public health sector albeit at unregulated fees. In Senegal and Uganda, governments established partnerships with private sector to manufacture COVID-19 rapid diagnostic tests. The private sector also contributed to treatment and management of COVID-19 cases. In addition, private entities provided personal protective equipment, conducted risk communication to promote adherence to safety procedures and health promotion for health service continuity. However, there were concerns related to reporting, quality and cost of services, calling for quality and price regulation in the provision of services. Conclusions The private sector contributed to the COVID-19 response through engagement in COVID-19 surveillance and testing, management of COVID-19 cases, and health promotion to maintain health access. There is a need to develop regulatory frameworks for sustainable public-private engagements including regulation of pricing, quality assurance and alignment with national plans and priorities during response to epidemics.